Design, synthesis and bioactivity evaluation of novel pyrazole linked phenylthiazole derivatives in context of antibacterial activity. (1st May 2021) - Patel, Bhautikkumar; Zunk, Matthew; Grant, Gary; Rudrawar, Santosh
Graphical abstract: Structure-activity relationship (SAR) study of 23 novel pyrazole linked phenylthiazole analogues was carried out. The most active compound 14b has shown promising antibacterial activity against the Gram-positive methicillin-resistant Staphylococcus aureus (MRSA, ATCC 43300) strain (MIC 4 μg/mL). The results of biological evaluation suggested that two crucial structural units are important for the anti-MRSA activity; i) the biphenylthiazole moiety at the C5 position of pyrazole and ii) the phenyl functional group linked with amide bond at C3 position of pyrazole. Abstract: Methicillin-resistant Staphylococcus aureus (MRSA) infections are a significant burden both clinically and economically worldwide. Increasing resistance to current antibiotics requires an urgent investigation into novel classes of antimicrobial agents. This study presents a structure–activity relationship (SAR) rationale for pyrazole linked phenylthiazole analogues as new antibacterial agents. A library of 23 novel pyrazole linked phenylthiazole compounds were synthesised, followed by screening for antimicrobial activity against five bacterial species and two fungi. The most active compound 14b has shown promising antibacterial activity against the Gram-positive methicillin-resistant Staphylococcus aureus (MRSA, ATCC 43300) strain (MIC 4 μg/mL). Furthermore, the active pyrazole linked phenylthiazole compound exhibited a better toxicity profile than standard antibiotics. In summary, these results demonstrate that a pyrazole linked phenylthiazole scaffold has potential as a lead for further investigation to afford novel antibacterial agents.